2019
DOI: 10.1371/journal.ppat.1007989
|View full text |Cite
|
Sign up to set email alerts
|

Memory CD4 T cell-derived IL-2 synergizes with viral infection to exacerbate lung inflammation

Abstract: Defining the most penetrating correlates of protective memory T cells is key for designing improved vaccines and T cell therapies. Here, we evaluate how interleukin (IL-2) production by memory CD4 T cells, a widely held indicator of their protective potential, impacts immune responses against murine influenza A virus (IAV). Unexpectedly, we show that IL-2-deficient memory CD4 T cells are more effective on a per cell basis at combating IAV than wild-type memory cells that produce IL-2. Improved outcomes orchest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 78 publications
5
41
2
Order By: Relevance
“…These results are surprising as we, and others, have previously shown that this regime of S4B6 IL-2C administration drives dramatic increases in CD8 T cells and NK cells in the spleen, with smaller increases in CD4 and γδ T cells, and a modest increase in total B cells 14 . To determine whether the decrease in PP B cells required CD122-targeted IL-2 signals we next treated mice for 3 days with either PBS alone or with IL-2C made using the JES6-1 antibody clone, which targets IL-2 to CD25-expressing cells.…”
Section: Resultscontrasting
confidence: 76%
See 2 more Smart Citations
“…These results are surprising as we, and others, have previously shown that this regime of S4B6 IL-2C administration drives dramatic increases in CD8 T cells and NK cells in the spleen, with smaller increases in CD4 and γδ T cells, and a modest increase in total B cells 14 . To determine whether the decrease in PP B cells required CD122-targeted IL-2 signals we next treated mice for 3 days with either PBS alone or with IL-2C made using the JES6-1 antibody clone, which targets IL-2 to CD25-expressing cells.…”
Section: Resultscontrasting
confidence: 76%
“…As part of our previous studies, we delivered S4B6 IL-2C systemically and investigated its impacts on immune cells in the spleen and lungs. We found, overall, that the general patterns observed in the spleen following S4B6 IL-2C administration were also seen in the lung, with increases in numbers of T cells and especially NK cells 14 . These results indicated that the regulation by IL-2 of major populations of immune cells present in secondary lymphoid organs and at mucosal sites is similar.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…IL-2 signals sustain the expression of STAT5 and Bcl-6, and promote expression of IL-7 receptor, thereby enabling the survival and maturation of CD4 + memory T cells [48,66]. Interestingly, however, IL-2-deficient memory CD4 + T cells generate a more vigorous and effective recall response against influenza virus than wild-type memory cells that produce IL-2 [67], suggesting that IL-2 and Bcl-6 may have regulatory or inhibitory roles once Ag-specific T cell memory has established, perhaps to prevent immunopathology during chronic antigen exposure. Of note, IL-2, IL-7, and IL-15, also known as common-gamma chain receptor cytokines, play key roles in memory (as well as in naïve and effector) CD4 + and CD8 + T cell development, homeostasis, and maintenance [68][69][70].…”
Section: T-bet the Master-regulator Of Th1 Cells Acts In An Expressmentioning
confidence: 99%
“…Natural Killer (NK) cells are a key component of the innate immune system and are critical in the response to many viral infections in humans and animal models (1)(2)(3). In addition to their beneficial antiviral role, NK cells have also been associated with immunopathology in infections such as respiratory syncytial virus (RSV) (4), influenza A virus (5)(6)(7)(8), and hepatitis B (9). Additionally, in the context of non-respiratory viral infections by HIV and HCV, NK cells appear to act as a rheostat by eliminating activated CD4+ and CD8+ T cells, thus preventing T cell-mediated autoimmunity (10).…”
Section: Introductionmentioning
confidence: 99%